Topografia convencional na aferição de áreas obtidas por georreferenciamento e Google Earth - Felipe, Alexandre Luis da Silva [UNESP] (2015)
The purpose of this study was to compare horizontal distances and areas of a polygon considering homologous points obtained through conventional survey using a Nikon Nivo total station 322d, a GNSS receiver AshTech Pro Mark 200 for georeferenced survey and Google Earth image. The processing of the survey made by computer program Datageosis Office version accused high precision constituting as the reference. The data obtained from the GNSS receiver were post-processed by the GNSS software Solution and the data obtained by Google Earth was submitted to the 13 AutoCAD software for drawing. The data obtained enabled the maps generation and calculation horizontal distances and areas in all three cases. It was possible to plot the three maps in a unique design by considering for the first point of the polygon obtained by conventional surveying, the same pair of coordinates obtained by the GPS receiver. It was concluded that the area value obtained through Google Earth being next to the reference value, does not means the polygon precision due to the fact of differences in distances sometimes the largest and sometimes the smallest being compensated, however it is possible to admit this procedure for use in general rural planning